2004
DOI: 10.1128/aem.70.8.4911-4920.2004
|View full text |Cite
|
Sign up to set email alerts
|

Change in Bacterial Community Structure during In Situ Biostimulation of Subsurface Sediment Cocontaminated with Uranium and Nitrate

Abstract: Previous studies have demonstrated that metal-reducing microorganisms can effectively promote the precipitation and removal of uranium from contaminated groundwater. Microbial communities were stimulated in the acidic subsurface by pH neutralization and addition of an electron donor to wells. In single-well pushpull tests at a number of treated sites, nitrate, Fe(III), and uranium were extensively reduced and electron donors (glucose, ethanol) were consumed. Examination of sediment chemistry in cores sampled i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
251
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(280 citation statements)
references
References 53 publications
20
251
2
3
Order By: Relevance
“…In these libraries, sequences that fell within subsurface clade 1 predominated, with subsurface clade 2 sequences of secondary importance (Figure 4). In a previous study conducted at a uraniumcontaminated aquifer in Oak Ridge, TN in which dissimilatory metal reduction was stimulated with the addition of either ethanol or glucose, there was also an enrichment of Geobacter species associated with increased metal reduction in sediments collected from this site (North et al, 2004). Analysis of the four 16S rRNA gene sequences that were reported for that community demonstrated that they all fell within Geobacter subsurface clade 1.…”
Section: Geobacter Metallireducens (L07834)mentioning
confidence: 99%
See 1 more Smart Citation
“…In these libraries, sequences that fell within subsurface clade 1 predominated, with subsurface clade 2 sequences of secondary importance (Figure 4). In a previous study conducted at a uraniumcontaminated aquifer in Oak Ridge, TN in which dissimilatory metal reduction was stimulated with the addition of either ethanol or glucose, there was also an enrichment of Geobacter species associated with increased metal reduction in sediments collected from this site (North et al, 2004). Analysis of the four 16S rRNA gene sequences that were reported for that community demonstrated that they all fell within Geobacter subsurface clade 1.…”
Section: Geobacter Metallireducens (L07834)mentioning
confidence: 99%
“…If so, then it may be feasible to predict the likely outcome of potential bioremediation strategies prior to implementation, making bioremediation a less empirical practice. This approach may be applicable to the in situ bioremediation of uranium-contaminated groundwater where stimulation of microbial U(VI) reduction generally results in significant enrichments of microorganisms closely related to known U(VI)-reducing Geobacter species that are responsible for the bioremediation process (Holmes et al, 2002Anderson et al, 2003;Petrie et al, 2003;North et al, 2004;Chang et al, 2005;Vrionis et al, 2005). This suggests that in silico models of Geobacter species (Mahadevan et al, 2006) might be able to predict how Geobacter species in the subsurface will respond to native geochemical conditions as well as amendments introduced into the subsurface that could enhance the bioremediation process.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular and culturing studies have demonstrated that Geobacter species are the predominant microorganisms in a wide diversity of subsurface environments in which dissimilatory Fe(III) reduction is an important process for the degradation of both natural organic matter and organic contaminants or for the stimulation of in situ bioremediation of metal-contaminated subsurface environments (Rooney-Varga et al, 1999;Anderson et al, 2003;Lovley et al, 2004;North et al, 2004;Coates et al, 2005;Lin et al, 2005;Sleep et al, 2006;Holmes et al, 2007;Winderl et al, 2007). By designing an isolation medium that mimics subsurface conditions, it has become possible to isolate Geobacter species that have 16S rRNA gene sequences that are identical or highly similar to the 16S rRNA sequences that predominate in Fe(III)-reducing subsurface environments Shelobolina et al, 2008;Holmes et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…The removal of U(VI) from groundwater following the in situ stimulation of metal reduction is often concomitant with substantial increases in the growth and activity of dissimilarity metalreducing microorganisms in the family Geobacteraceae (4,6,7,9). Despite extensive efforts to understand the mechanisms and pathways used by these bacteria to reduce U(VI), the nature of its U reductase has remained elusive for almost two decades.…”
mentioning
confidence: 99%
“…Some can also use uranium (U) as an electron acceptor (1,2), a process that could be harnessed for the bioremediation of the contaminated aquifers and sediments left by the intensive U mining practices of the Cold War era (3). Interestingly, stimulating the activity of metal-reducing microorganisms in situ resulted in the concomitant removal of soluble hexavalent uranium [U(VI)] from the contaminated groundwater and detection of its sparingly soluble, less mobile form, tetravalent uranium [U(IV)] in sediments (4)(5)(6)(7)(8). This suggests that stimulating metal reduction in the subsurface results in the biological reduction of U(VI) to U(IV), thereby preventing plume migration and eliminating the potential for contaminant exposure.…”
mentioning
confidence: 99%